Quality of Midwife-provided Intrapartum Care in Amhara Regional State, Ethiopia - Tegbar Yigzaw; Fantu Abebe; Lalem Belay; Yewulsew Assaye; Equlinet Misganaw; Ashebir Kidane; Desalegn Ademie; Jos van Roosmalen; Jelle Stekelenburg; Young-Mi Kim (BMC, 2017)
Abstract Background Despite much progress recently, Ethiopia remains one of the largest contributors to the global burden of maternal and newborn deaths and stillbirths. Ethiopia's plan to meet the sustainable development goals for maternal and child health includes unprecedented emphasis on improving quality of care. The purpose of this study was to assess the quality of midwifery care during labor, delivery and immediate postpartum period. Methods A cross-sectional study using multiple data collection methods and a 2-stage cluster sampling technique was conducted from January 25 to February 14, 2015 in government health facilities of the Amhara National Regional State of Ethiopia. Direct observation of performance was used to determine competence of midwives in providing care during labor, delivery, and the first 6 h after childbirth. Inventory of drugs, medical equipment, supplies, and infrastructure was conducted to identify availability of resources in health facilities. Structured interview was done to assess availability of resources and performance improvement opportunities. Data analysis involved calculating percentages, means and chi-square tests. Results A total of 150 midwives and 56 health facilities were included in the study. The performance assessment showed 16.5% of midwives were incompetent, 72.4% were competent, and 11.1% were outstanding in providing routine intrapartum care. Forty five midwives were observed while managing 54 obstetric and newborn complications and 41 (91%) of them were rated competent. Inventory of resources found that the proportion of facilities with more than 75% of the items in each category was 32.6% for drugs, 73.1% for equipment, 65.4% for supplies, 47.9% for infection prevention materials, and 43.6% for records and forms. Opportunities for performance improvement were inadequate, with 31.3% reporting emergency obstetric and newborn care training, and 44.7% quarterly or more frequent supportive supervision. Health centers fared worse in provider competence, physical resources, and quality improvement practices except for supportive supervision visits and in-service training. Conclusions Although our findings indicate most midwives are competent in giving routine and emergency intrapartum care, the major gaps in the enabling environment and the significant proportion of midwives with unsatisfactory performance suggest that the conditions for providing quality intrapartum care are not optimal.